2013
DOI: 10.1037/a0034596
|View full text |Cite
|
Sign up to set email alerts
|

Eyewitness confidence in simultaneous and sequential lineups: A criterion shift account for sequential mistaken identification overconfidence.

Abstract: Confidence judgments for eyewitness identifications play an integral role in determining guilt during legal proceedings. Past research has shown that confidence in positive identifications is strongly associated with accuracy. Using a standard lineup recognition paradigm, we investigated accuracy using signal detection and ROC analyses, along with the tendency to choose a face with both simultaneous and sequential lineups. We replicated past findings of reduced rates of choosing with sequential as compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
90
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(112 citation statements)
references
References 65 publications
15
90
2
Order By: Relevance
“…Thus, it seems fair to conclude that the signal detection analyses weigh against the notion that sequential lineups are diagnostically superior to simultaneous lineups. To the extent that these findings are interpreted as supporting the simultaneous procedure, they are consistent with recent laboratory-based ROC analyses (18)(19)(20)(21).…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…Thus, it seems fair to conclude that the signal detection analyses weigh against the notion that sequential lineups are diagnostically superior to simultaneous lineups. To the extent that these findings are interpreted as supporting the simultaneous procedure, they are consistent with recent laboratory-based ROC analyses (18)(19)(20)(21).…”
Section: Resultssupporting
confidence: 67%
“…4A). In addition, and again contrary to a widely held view, the present results reinforce both ROC analyses of laboratory-based data (18)(19)(20)(21) and another police department field study analysis (22) suggesting that sequential lineups are not diagnostically superior to simultaneous lineups and that the reverse is more likely to be true (although, depending on how the data were analyzed here, the simultaneous advantage was not always significant).…”
Section: Discussioncontrasting
confidence: 36%
See 2 more Smart Citations
“…In fact, research has provided strong evidence that eyewitness confidence in identifications may in fact be the greatest predictor of verdict outcomes at trial (Cutler et al, 1990), with reliance on witness confidence shown to be unaffected by traditional safeguards, such as cross-examination . Within the United States, the Supreme Court held that the confidence of eyewitness testimony can be used as a measure of its reliability, alongside determining whether such evidence can be considered admissible during trial (see Dobolyi & Dodson, 2013).…”
Section: Eyewitness Confidencementioning
confidence: 99%